Al-Qur’an dan Pluralisme Agama: Perspektif Mahmoud Musthafa Ayoub - Adi Fadli (Universitas Islam Negeri Mataram, 2005)
Islam is revealed by God in order to put human life in the right order in which they can reach and make justice, peace, welfare, and salvation of life. To make all those ideal objectives come true Muslims need some method of interpretation to the Qur’an, as ultimate Islamic normative base, to have it be in mutual accord with its real social-cultural context. It must be done in respective to its current epistemological development so that every methods developed in this subject is scientifically and methodologically acceptable. One of modern Muslim thinkers in this area is Mahmoud Musthafa Ayoub who tries to find out new interpretation method to the sacred texts of Qur’an in relation to religious pluralism. His way of interpretation asserted the Islamic tendency toward dialogue efforts in solving any problems related to religious pluralism. His way differs from most Muslims’ way that tends to make the ideal massage of Islam untouchable. He concludes that Islam wants Muslims to continuously make interreligious dialogue, especially with its two older brothers in Abrahamic religions—Jews and Christian.